Bone marrow-derived mesenchymal stromal cell: what next? - Borges FT (Dove Medical Press, 2018)
Fernanda T Borges,1,2 Marcia Bastos Convento,1 Nestor Schor1,† 1Nephrology Division, Department of Medicine, Universidade Federal de São Paulo, São Paulo, SP, Brazil; 2Interdisciplinary Postgraduate Program in Health Sciences, Universidade Cruzeiro do Sul, São Paulo, SP, Brazil †Professor Nestor Schor passed away on February 2, 2018 Abstract: Bone marrow mesenchymal stromal cell (MSC) is a potential alternative in regenerative medicine and has great potential in many pathologic conditions including kidney disease. Although most of the studies demonstrate MSC efficiency, the regenerative potential may not be efficient in all diseases and patients. Stem cell feasibility is modified by donor characteristics as gender, age, diet, and health status, producing both positive and negative results. The conditioning of MSC can potentiate its effects and modify its culture medium (CM). In current practices, the cell-free treatment is gaining notable attention, while MSC-conditioned CM is being applied and studied in many experimental diseases, including, but not limited to, certain kidney diseases. This may be the next step for clinical trials. Studies in stem cell CM have focused mainly on extracellular vesicles, nucleic acids (mRNA and microRNA), lipids, and proteins presented in this CM. They mediate regenerative effects of MSC in a harmonic manner. In this review, we will analyze the regenerative potential of MSC and its CM as well as discuss some effective techniques for modifying its fractions and improving its therapeutic potential. CM fractions may be modified by hypoxic conditions, inflammation, lipid exposition, and protein growth factors. Other possible mechanisms of action of stem cells are also suggested. In the future, the MSC paracrine effect may be modified to more closely meet each patient’s needs. Keywords: mesenchymal stromal cells, secretome, extracellular vesicles, microRNAs, lipids, growth factor